Erratum: Structure analysis of two Toxoplasma gondii and Neospora caninum satellite DNA families and evolution of their common monomeric sequence (Journal of Molecular Evolution) (2004) 58 (557-567)) - Clemente, M. (2004)
Fil:Clemente, M. Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales; Argentina.